Comparison between lignin extraction by alkaline and ultrasound-assisted alkaline treatment from oil palm empty fruit bunch - Toma, Farhana Sultana; Zulkifly, Jemaat; Beg, M. D. H.; Khan, M R; R. M., Yunus (IOP Publishing, 2021)
Lignin is the second most abundant terrestrial biopolymer after cellulose and is the largest renewable source of aromatic groups in nature. In this work, the study was carried out on the selective extraction of lignin from oil palm empty fruit bunch (OPEFB) using alkaline and ultrasound-assisted alkaline methods. OPEFB is available in high amounts as solid waste of palm oil industries, which is considered as lignocellulosic and has fairly high lignin content. The pretreatment of OPEFB for lignin production depends on the effect of particle size, liquid to solid ratio, the concentration of NaOH, reaction temperature, type of solvent, and sonication time. OPEFB was treated with 7.5%, 10%, and 15% NaOH at 900C for 1.5h without ultrasound irradiation and with ultrasonic time for 10, 20, 30, and 40 min. Extracted lignin was characterized by FT-IR, UV-Vis, TGA, and elemental analysis. Considerably improved results were obtained by using the ultrasound-assisted time for 30 min. The percentage yield and purity of lignin extracted by the ultrasound-assisted alkali method was higher than that lignin fraction which was achieved by the alkali method, and their purity was improved with the addition of sonication time from 10 to 30 min.